Improved Bacterial Foraging Algorithm for Optimum Economic Emission Dispatch with Wind Power - Sajjad Farajianpour; Ali Mohammadi; Saeed Tavakoli; S. Masoud Barakati (Universitas Ahmad Dahlan, 2012)
In this paper, an improved bacterial foraging algorithm (IBFA) is employed to solve economic-emission dispatch (EED) problem. Regarding to more interest to renewable energy sources especially wind energy in recent years, it is necessary to use of incorporate wind power plants into EED problem. To consider realistic conditions, EED is included bi-objective of cost and NOx emission. The problems encountered with BFA are ineffective bacteria elimination resulted in poor performance. To overcome this, a modified BFA is proposed in reproduction step termed as Improved Baterial Foraging Algorithm (IBFA). EED is solved, with wind power plant and without it, subjected to couple of constraintsusing BFA an BFA in a comparative manner.Simulation results show enhancement in convergence accuracy with IBFA rather than conventional BFA.